Crecimiento y calidad de las plantas de Carapa guianensis “andiroba” en la plantación n°04 de tres años de edad. CIEFOR - Puerto Almendra, Loreto – Perú. 2022 - Pérez Güibin, Roxana Jazmin (2024)
The study aimed to evaluate the growth and quality of Carapa guianensis plants in a three-year-old plantation located at the UNAP Center for Forestry Research and Education. On average, the plants showed a diameter increase of 5.87 mm and a height growth of 34.88 cm. The plantation's survival rate was high, reaching 96%, with a mortality rate of 4%. Regarding plant quality, the majority (88.02%, equivalent to 169 seedlings) were classified as GOOD, while the remaining 11.98% (23 seedlings) were rated as AVERAGE. The analysis of variance indicated no significant differences in the average diameter growth among the different strips; however, significant differences were observed in the average height growth. It is recommended to continue biometric evaluations of the plantation and conduct periodic maintenance to ensure its long-term health and productivity.